Bandwidth Management Mechanisms for Ethernet Passive Optical Networks with Multi-ONU Customers - Ciceri Coral, Oscar Jaime; Fonseca, Nelson Luis Saldanha (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
Passive optical network (PON) is a cost-efficient access network technology to deliver broadband services. Moreover, service providers employ PONs to offer novel services. New business scenarios are, thus, envisioned in which customers owning multiple optical network units (ONUs) are connected to a single PON (multi-ONU customers). This paper proposes a dynamic bandwidth allocation (DBA) algorithm to guaranteed bandwidth for multi-ONU customers in Ethernet PONs (EPONs). It also introduces a bandwidth sharing algorithm to support cooperation among customers. Results show that the proposed algorithm can improve the overall throughput and quality of service provisioning.